SARS-CoV-2 vaccine breakthrough infection and the evaluation of safety precaution practice before and after vaccination among healthcare workers in South West, Nigeria - Oluwatosin Idowu Oni; Patrick Olanrewaju Osho; Tayelolu Mary Odesanmi; Habeebat Motunrayo Raji; Faith Titilayo Oluranti; Demian Ibina (BMC, 2024)
Abstract Introduction Worldwide, it has been reported that fully vaccinated people still die of COVID-19-associated symptoms, generating public uncertainty about the safety and effectiveness of the vaccines. Hence, this research is aimed at assessing the incidence of COVID-19 breakthrough infection among vaccinated Health Workers and the possible effect of changes in the practice of post-vaccination safety precautions. Method This was a Health facility-based descriptive cross-sectional study. Data were collected using self-administered questionnaires distributed at the participant's work unit across the selected health facilities. The nasopharyngeal specimen was also obtained from the participants and analysed using STANDARD Q COVID-19 Ag Test rapid chromatographic immunoassay for the detection of antigens to SARS-CoV-2. All data were input and analyzed using SPSS version 20. Results There was a statistically significant relationship between the vaccination status of respondents and the post-vaccination test result (χ2 = 6.816, df = 1, p = 0.009). The incidence of COVID-19 infection among the vaccinated and unvaccinated HCWs was 2% and 8% respectively. 5 of the 15 respondents who tested positive for COVID-19 had been fully vaccinated. However, all 5 of them did not practice safety measures after vaccination. None of the respondents who practised safety measures after vaccination tested positive for COVID-19. The remaining 10 respondents that tested positive for COVID-19 had not been vaccinated though they practised safety precautions. Conclusion Vaccination and the practice of safety precautions will go a long way to preventing future COVID-19 breakthrough infections.